How does intimate partner violence affect contraceptive use among women in the Philippines? - De Guzman, Joaquin Domingo S.; Lobo, Kristoffer John Ronald Y.
The study looks at the relationship of intimate partner violence (IPV) on modern and traditional contraceptive use among sexually active women in the Philippines aged 15-49 years old who are married or in consensual union. Logistic regressions were done separately for contraceptives (use/non-use), modern contraceptives (use/non-use), and traditional contraceptives (use/non-use) on a pooled sample from the National Demographic Health Survey or NDHS of 2008 (n=4,725), 2013 (n=5,221), and 2017 (n=8,548). The results show that those experiencing any types of IPV (dy/dx = 4%, p<0.01) are more likely to use contraceptives while those experiencing physical violence (dy/dx = 3%, p<0.01) and psychological violence (dy/dx = 2%, p<0.05) separately had the same positive relationship. For the regression that used interactions between the types of IPV, experiencing physical and psychological IPV (dy/dx = 3%, p<0.05) makes it more likely to use contraceptives while physical and sexual IPV (dy/dx = -5%, p<0.10) had a negative relationship with contraceptive use. These relationships were consistent with the regressions for modern and traditional contraceptives except for physical and sexual IPV which was only significant for traditional contraceptive use (dy/dx = -7%, p<0.10). The findings emphasize the importance of factoring in abuse in health policies and providing health services. It recommends the continuation of family planning programs and projects addressing IPV, such as counselling.